Descriptions of 19 Unrecorded Species Belonging to Sordariomycetes in Korea - Thuong T. T. Nguyen; Hyang Burm Lee (Mycobiology)
A survey of fungal diversity in soil and freshwater habitats in Korea isolated several species of the class Sordariomycetes. Morphological characteristics and multigene phylogenetic analyses showed that these species represented new records for Korea. Herein, we report the descriptions, illustrations, and molecular phylogeny of 19 species previously undescribed in Korea, including Achaetomiella virescens, Arxotrichum gangligerum, Caespitomonium euphorbiae, Comoclathris typhicola, Gamsia aggregata, Luteonectria nematophila, Paramyrothecium sinense, Parasarocladium debruynii, Pleurocordyceps agarica, Pyrenochaetopsis sinensis, Scedosporium boydii, Scedosporium dehoogii, Scedosporium minutisporum, Striatibotrys rhabdosporus, Trichocladium crispatum, Trichoderma azevedoi, Trichoderma longifialidicum, Xepicula leucotricha, and Xylomelasma sordida.